Vitamin D and immuno-pathology of COVID-19: many interactions but uncertain therapeutic benefits - Banerjee, Anindita (Expert Rev Anti Infect Ther, 2021)
Introduction: COVID-19 pandemic has caused huge loss of human lives and extensive socio-economic damages. The immuno-pathology of this disease is neither clearly understood nor there are effective drugs for severe cases of COVID-19. Repurposing of available drugs for the treatment of COVID-19 is imperative. Areas Covered: This review has gathered the evidence from PubMed, Google Scholar, WHO, and other reliable websites on COVID-19 and summarized the existing knowledge of the immuno-pathology of COVID-19. We elucidated how vitamin D through its diverse actions on immune effector cells, epithelial cells, or renin-angiotensin-aldosterone system could have a modulatory role on the pathogenic mechanisms of COVID-19. The epidemiological evidence associating vitamin D deficiency with the severity and incidence of COVID-19 is also presented. However, the evidence of clinical benefit to patients of COVID-19 from randomized controlled trials with vitamin D has not come as yet. Expert opinion: It is now established that fatality of COVID-19 is primarily determined by hyperactivation of the host’s innate immune system in response to SARS-CoV-2 invasion, and thus the research on the immuno-modulatory and other roles of vitamin D against viral infections should be pursued vigorously. This would be also useful for future pandemics caused by other novel viruses.